Efficacy and safety of Rosuvastatin versus Atorvastatin in patients with Hypercholestrolemia - S.S, Sanket; I.S, Anand (Indian Journal of Pharmacy Practice)
The objective of the study was to measure efficacy and safety of Rosuvastatin-10mg versus Atorvastatin-20mg in patients with Hypercholesterolemia. We conducted a single centre retrospective study, involving 117 hypercholesterolemia patients between age group of 45-80 years. Data of both diabetic and nondiabetic patients with LDL-C: ≥140 - < 250 mg/dl, HDL-C: < 40 - >60 mg/dl, Total Cholesterol: 200-240 mg/dl, Triglyceride: ≥165-≤400 mg/dl and VLDL: <5- >40 mg and who were prescribed either Rosuvastatin 10mg or Atorvastatin 20mg were included in the study. Astatistically significant reduction in LDL-C, TG, TC and VLDL was seen in both the groups. Similarly a statistically significant increase in HDL-C levels was observed in both the groups. Rosuvastatin showed a statistically significant reduction in TG at week 12 as compared to Atorvastatin. Decrease in LDL-C, TC, TG and VLDL was 22.3%, 16.3%, 30.1% and 31% respectively in Rosuvastatin group while the reduction was 15.5%, 13.7%, 19.2% and 23.4% respectively in Atorvastatin group. Rosuvastatin showed a greater improvement in lipid parameters as compared to Atorvastatin though this difference was not statistically significant. Both treatments were well tolerated with similar incidence of adverse events (Rosuvastatin 10 mg: 6.25% as compared to Atorvastatin 20 mg: 7.55%).Rosuvastatin was more effective than Atorvastatin in reducing LDL-C, Total Cholesterol, Triglyceride and VLDL. It was also better in increasing HDL-C as compared to Atorvastatin. Rosuvastatin therefore seems to be a better alternative from other statins in patients having Hypercholesterolemia.
Keywords: Rosuvastatin; Atorvastatin; Hypercholesterolemia